State, market and civil society in Philippine Public Administration - Cariño, Ledivina V. (Philippine journal of public administration)
The author critically limns the roles of the state, market and civil society in the development of the discipline of Public Administration (PA) and how these roles can help PA move forward. Doing this, she takes the reader on a time trip, from the 1880s of Woodrow Wilson to the present, navigating four streams, namely, Traditional Public Administration (TPA), Development Administration (Dev Ad), New Public Administration (New PA), and Public Administration and Governance (PAG). The article explores the voyages essayed by the meaning of the word "public" in "public administration." This little exploration (the author's own words), shunning proclamation of both great worth and contribution of her work, offers five lessons. All five have to do with the impact of state, market and civil society on the theories and concepts of Philippine Public Administration (PPA).